Currency Unions, the Phillips Curve, and Stabilization Policy: Some Suggestions for Europe - Thomas I. Palley (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2006)
This paper examines the implications of a currency union for monetary policy. The formation of a currency union worsens the inflation-unemployment tradeoff, so that leaving the inflation target unchanged at its pre-currency union level generates increased unemployment. Geographically based fiscal automatic stabilizers can improve the inflation-unemployment trade-off, which has bearings on the Euro area's Stability and Growth Pact. Financial intermediary balance sheet regulation based on asset-based reserve requirements (ABRR) can provide additional country-specific policy instruments. ABRR alleviate the targets and instruments problem afflicting the monetary authority in a currency union context. This is important for the European Central Bank, which is trying to manage divergent country growth rates with a single interest rate instrument.
Keywords: E5; 330; currency unions; Phillips curve; monetary policy; fiscal policy; asset based reserve requirements